Evaluative Wortbildung und Personenreferenz. : Maskulina auf -i und ihre femininen Entsprechungen in alemannischen Dialekten – auch als Indikator für Geschlechterstereotype im Wörterbuch - Dammel, Antje (Linguistik Online, 2021)
The word formation pattern [ __-i]N mask. in Alemannic mainly derives masculine agent nouns from verbs resulting in output semantics of ‘someone who notoriously acts in the manner of base verb’. I analyse the pattern as an instance of evaluative morphology embedded in a more general output oriented schema and propose a scenario how the pattern may have developed from an OHG hypochoristic pattern primarily used in names. In a qualitative and quantitative analysis of two dialect dictionaries on Zürich German and Bernese German I look into the possible lexical fillings of the pattern and derive areas of stereotypisation. As the products of the pattern are masculine nouns, it is of interest whether the lemmas are flanked with a feminine form or not, and if they are, whether the feminine form follows or precedes the masculine form or is added as a separate lemma without a masculine pendant. The analysis also includes neuter forms ending in -i listed in the dictionaries. As the masculine products of the pattern already reflect stereotyped behaviour, the feminine (and neuter) forms included in the dictionnaries are expected to sediment gender stereotypes to a high degree.